Analyzing the role of social emotional learning principles in cultivating tolerance among elementary school - Retnasari, Lisa; Wardani, Ella Kusuma; Suyitno, Suyitno; Sulaiman, Sulaiman; Fathurrohman, Fathurrohman (EduStream: Jurnal Pendidikan Dasar, 2026)
Intolerance is a crucial issue that threatens social cohesion, especially in primary education environments, which is the foundation for character building. This study aims to analyze in depth the role of Social Emotional Learning (SEL) principles on the formation of students’ attitudes of tolerance in elementary schools. The research approach used was a mixed methods approach with a sequential explanatory design. Quantitative data was collected through questionnaires distributed to 125 students, while qualitative data was obtained through focus group discussions (FGD) involving seven teachers. Quantitative data were analyzed using descriptive statistics to capture the level of SEL competency achievement, while qualitative data were analyzed thematically to identify patterns of SEL contribution. The research findings indicate variations in the achievement of SEL competencies; social awareness and self-awareness competencies are in the moderate category, while responsible decision-making competencies are in the low category. Further thematic analysis reveals four main contributions of SEL practices to tolerance, namely: (1) as a conflict management strategy, (2) internalized through the hidden curriculum, (3) formed through a habit-forming mechanism, and (4) facing pedagogical structural challenges. The implications of the research are in the form of a comprehensive SEL principles integration model, covering three fundamental aspects: strengthening teacher capacity, integrating.